PENGARUH KOMPETENSI SDM DAN IMPLEMENTASI AKUNTANSI AKRUAL TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Wijayanti, Ratna; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test the influence of the competence of human resources and the implementation accrualbased accounting to the quality of local financial statement at the District government of Madiun. The data isthe primary data. The sources of the data which has been used are the results of the filling in of questionnaires bythe respondents.The respondents in this research is the head of department, head office and chief financial officerin the of SKPD of the district goverment Madiun. 39 questionnaires which have been distributed, only 30 havereturned and can be processed. The data analysis in this research has been done by using the SPSS applicationassistance program (Statistical Product and Service Solution) version 20.0.The result of the research shows thatthe competence of human resources does not give any positive influence to the quality of the local financialreporting since its significance level is 0.237 > 0.05. Meanwhile the implementation of accrual based accountinggive positive influence to the quality of the local financial reporting with its significant level is 0.000.Keywords: The Competence Human Resources, the Implementation of Accrual Based Accounting, the Qualityof Financial Reporting Area